Isolasi dan Pengaruh Monosodium Glutamat terhadap Pertumbuhan Bakteri Proteolitik Limbah Cair Tahu - Cahyaningrum, Emi; Wijanarka, W; Lunggani, Arina Tri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2021)
The tofu industry in Indonesia is growing rapidly. Tofu liquid waste is usually discharged into the waters and causes water pollution. An efficient way to overcome this problem is to utilize tofu liquid waste. Tofu liquid waste contains proteolytic bacteria that are useful in industry. The increase in bacterial growth is done by adding substances, one of which is the addition of Monosodium Glutamate (MSG). MSG contains glutamate which plays a role in protein synthesis. This study aims to isolate proteolytic bacteria and determine the effect of MSG on the growth of proteolytic bacteria in tofu liquid waste. The research methods included isolation, purification, morphological characterization, calculation of the Proteolytic Index (IP), testing the effect of MSG concentration on growth and protease activity, and data analysis. The MSG concentration used was 0 gr/L; 0.5 gr/L; 1 g/L and 1.5 g/L. The design used was Completely Randomized Design (CRD). The results obtained four isolates with different morphological characteristics. The isolate that had the highest IP value was the fourth isolate of 3,206 and was used for the test. The effect of MSG on growth and protease activity was highest at a concentration of 1.5 g/L at 24 hours. The highest protease enzyme activity was 0.0756 U/mL. The results of the ANOVA analysis showed a significant effect (p<0.05) on the administration of MSG on the growth of the four proteolytic bacterial isolates of tofu wastewater